PENINGKATAN MUTU PELAYANAN MELALUI PENGUATAN KAPASITAS TENAGA KESEHATAN DI DINAS KESEHATAN KABUPATEN DAIRI - Yustina, Ida; Siregar, Fazidah Aguslina; Aini, Fadilah (Jurnal Salam Sehat Masyarakat (JSSM), 2024)
Dairi District Health Office North Sumatra Province is a type A health service that oversees 18 Health Centers recorded from the Community Health Development Index (IPKM) 2018, which is at a value of 0.6044, and this still does not meet the indicator set by the Ministry of Health of 0. 6087, it is assumed that the IPKM is 0. indicator set by the Ministry of Health 0. 6087, it is assumed that the low IPKM is caused by the low quality of services provided by the health centers. low GPA is caused by the low quality of services provided by health workers in Dairi Regency. health workers in Dairi Regency. This service aims to improve the quality ofservices of health workers at the Dairi District Health Office through capacity building and planning. capacity building and planning. The targets in this service were 50 health workers at the Dairi Regency Health Office. The results of the service are shown by the existence of planning documents prepared by health workers at the puskesmas level. As an effort to improve quality of health services, monitoring and evaluation of health workers is needed, especially health workers, especially from health centers.